If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1n + 2)(2n + 5) = 0 Reorder the terms: (2 + 1n)(2n + 5) = 0 Reorder the terms: (2 + 1n)(5 + 2n) = 0 Multiply (2 + 1n) * (5 + 2n) (2(5 + 2n) + 1n * (5 + 2n)) = 0 ((5 * 2 + 2n * 2) + 1n * (5 + 2n)) = 0 ((10 + 4n) + 1n * (5 + 2n)) = 0 (10 + 4n + (5 * 1n + 2n * 1n)) = 0 (10 + 4n + (5n + 2n2)) = 0 Combine like terms: 4n + 5n = 9n (10 + 9n + 2n2) = 0 Solving 10 + 9n + 2n2 = 0 Solving for variable 'n'. Factor a trinomial. (5 + 2n)(2 + n) = 0Subproblem 1
Set the factor '(5 + 2n)' equal to zero and attempt to solve: Simplifying 5 + 2n = 0 Solving 5 + 2n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2n = 0 + -5 2n = 0 + -5 Combine like terms: 0 + -5 = -5 2n = -5 Divide each side by '2'. n = -2.5 Simplifying n = -2.5Subproblem 2
Set the factor '(2 + n)' equal to zero and attempt to solve: Simplifying 2 + n = 0 Solving 2 + n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + n = 0 + -2 n = 0 + -2 Combine like terms: 0 + -2 = -2 n = -2 Simplifying n = -2Solution
n = {-2.5, -2}
| 14=2a-6 | | -5t^2+40t+60=0 | | x^2+2x^2-125=0 | | 4x^2-40x+45=0 | | 23x-12= | | 0.8x+20-4.5=5+x-0.9x | | 7a+5a=4(a-8)+12(a+9) | | 2(4x-1)+1=20 | | 2n-2=n-8 | | X^2+12x+y^2+4y=60 | | 7y+8=68 | | 6x=333334y | | 10x-7x=84 | | 7y+x=-20 | | 5h+7=3(2h-1) | | X+7y=-20 | | k/2+1=k/3-1 | | x+35+35=180 | | -8=y-6 | | 8(n-3)-(2-n)= | | 5[h+2]=3[j-1] | | 3x(X+1)-3x= | | -9+w=-7 | | 4x+-9+-9y=6 | | -9=u+9 | | .5(100+A)=50 | | x(-53-15x)=0 | | 6+2(3e-1)= | | 29=-2(4x-5)+3(3x+6) | | 2-12x+6=0 | | 4x-7=2b+X | | 12p-7=8p+9 |